1997
DOI: 10.1042/bst0250783
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of xanthine dehydrogenase into oxidase and its role in reperfusion injury

Abstract: Xanthine dehydrogenases from various sources are proteins of molecular mass 300 kDa and are composed of two identical independent subunits; each subunit contains one molybdopterin, two non-identical 2Fe/2S centres and FAD [ 1,2]. T h e mammalian enzyme exists originally as xanthine dehydrogenase, but is converted into xanthine oxidase during extraction or purification procedures [3]. Xanthine dehydrogenase is characterized by high xanthine/NAD+ activity and low xanthine/Oz activity, whereas xanthine oxidase is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 4 publications
2
29
0
2
Order By: Relevance
“…Most interest was mainly focused on freeradical metabolism, mediated through hypoxanthine/xanthine oxidation by XO, in biochemical mechanisms associated with a wide variety of human diseases. This ''new'' ROS-generating pathway, of XOR and NADH, must then be reevaluated in those clinical conditions where an increase in NADH is expected, such as in diseases where hypoxic and reperfusion cycles exist, in ethanol hepatotoxicity and in diabetes [12,14,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interest was mainly focused on freeradical metabolism, mediated through hypoxanthine/xanthine oxidation by XO, in biochemical mechanisms associated with a wide variety of human diseases. This ''new'' ROS-generating pathway, of XOR and NADH, must then be reevaluated in those clinical conditions where an increase in NADH is expected, such as in diseases where hypoxic and reperfusion cycles exist, in ethanol hepatotoxicity and in diabetes [12,14,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Normal processes of metabolism continuously form ROS, and many of them may have useful physiological functions, such as in host defence against invading pathogens, and as mediators of signal transduction [10,11]. Their overproduction, however, can play a major role in several pathological conditions [12][13][14][15][16]. Moreover, it was recently shown that XOR can catalyse the reduction of nitrates and nitrites, giving rise to both • NO [17,18] and peroxynitrite (ONOO -) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Inherited XOR deficiency leads to xanthinuria and a characteristic multiple organ failure syndrome characterized by the deposition of xanthine in various tissues. The detailed biochemistry of XO and XDH conversion of XDH to XO has been subject to several reviews and research papers (Nishino, 1994;Nishino et al, 1997Nishino et al, , 2005Pritsos, 2000;Borges et al, 2002;Ilich and Hille, 2002;McManaman and Bain, 2002;Meneshian and Bulkley, 2002). It is interesting to note that recent work has shown that XO is regulated on the transcriptional and post-transcriptional levels (Hoidal et al, 1997;Terada et al, 1997;Hassoun et al, 1998;Page et al, 1998;Xu et al, 2000;Ghio et al, 2002).…”
Section: Introduction Historical Backgroundmentioning
confidence: 99%
“…generation, however, was suggested to increase when the apparent ratio of XDH to XO changes. That is, as XDH is inhibited by the accumulated NADH during ischemia, accumulated hypoxanthine is utilized more by XO than would be the case under normal conditions, and increased superoxide production may occur upon reperfusion even though conversion from XDH to XO does not take place (41,42 …”
Section: Fig 6 Reactivation Of Cn-and No-treated Xomentioning
confidence: 99%